Risk Stratification of Dysphagia After Surgical Treatment of Hypopharyngeal Cancer - Joo, Hye Ah; Lee, Yoon Se; Jung, Young Ho; Choi, Seung-Ho; Nam, Soon Yuhl; Kim, Sang Yoon (Frontiers in Surgery, 2022)
Objective: Hypopharyngeal cancer is managed by either surgical resection or radiation therapy-based treatment. In choosing the treatment modality, the patient’s swallowing function should be considered to achieve optimal treatment outcomes. This study aimed to stratify the risk factors predictive of postoperative dysphagia in hypopharyngeal cancer. Study Design: Retrospective study Setting: Tertiary referral center Methods: We enrolled 100 patients who were diagnosed with hypopharyngeal cancer and underwent curative surgery between January 2010 and December 2019, and retrospectively reviewed their medical records. Results: Postoperative dysphagia occurred in 29 patients (29%) who required a tracheostomy tube or percutaneous gastrostomy tube for feeding or preventing aspiration; additionally, the overall survival rate was lower in those patients than in those without dysphagia. The univariate analysis revealed that postoperative dysphagia was associated with clinical T stage (p = 0.016), N stage (p = 0.002), and surgical resection extent of the larynx and pharynx (p < 0.001). Patients who underwent total laryngectomy with total/partial pharyngectomy were more likely to have dysphagia than those in the larynx-preserving pharyngectomy groups (odds ratio [OR] = 3.208, 95% confidence interval [CI] 1.283–8.024, p = 0.011). Concerning the posterior pharyngeal wall (PPW), which has an important role in swallowing, patients who underwent resection of ≥ 1/2 of the PPW were more likely to have dysphagia (OR = 7.467, 95% CI 1.799–30.994, p = 0.003). Conclusions: Surgical resection extent was proportionally associated with dysphagia in hypopharyngeal cancer patients. Patients with smaller lesions but no laryngeal invasion had better postoperative swallowing function than patients with larger lesions or laryngeal involved lesions. Preserving the larynx and hypopharyngeal mucosa (especially the PPW) as much as possible can help preserve postoperative swallowing function.